An investigation of the Sustainability of Village Savings and Loans Associations (VSLAs) amidst Covid-19 and its impact on household income levels: lessons from Malawi, Sub-Saharan Africa - Munthali, George N. Chidimbah; Wu, Xuelian; Dzimbiri, Mastano Nambiro Woleson; Zolo, Amon; Mushani, John K.B.; Banda, Lazarus Obed Livingstone (BMC PUBLIC HEALTH, 2022)
Background: Food security, malnutrition, and poverty are some of the challenges that most of the sub-Saharan African countries have been historically facing. With the coming of Covid-19 pandemic, the sustainability of the Village Savings and Loans Association which are formed to counter fght these challenges is questioned. Aim: This study aimed to assess factors associated with the Sustainability of VSLAs amidst Covid-19 and its impacts on households’ income levels. Methods: An online cross-sectional design was conducted from November to January 2021, targeting VSLAs mem bers in Mzuzu. A snowball and respondent-driven sampling technique were used to recruit the needful participants using a referral approach. IBM SPSS version 23 was used to perform descriptive statistics, Chi-Square, and binary logistic regression with unstandardized Beta (β), Odds Ratios (OR), and 95% Confdence Interval (CI) being taken into account with P-value set at 0.1, 0.05 and 0.01 signifcance levels. Results: Our study fnds that household income declined by 54% for those earnings belonged to ˂ MK5,000, as compared to 38% and 15% for medium (MK5,000≥MK10,000) and higher (>MK10,000) income bands respectively. Our study shows that gender (β=0.437, p=0.094), age-group (β=1.317, p=0.000), education (β=2.181, p=0.047), share contributions (β=1.035, p=0.008), meetings (β=0.572, p=0.021), occupation (β=-0.453, p=0.106), and fre quency of meeting (β=-0.507, p=0.049) were positively and negatively statistically signifcant predictors. Conclusion: According to the fndings of this study, households with lower income earners, which is one of the indicators of poverty, are more afected by the pandemic than their counterparts. We urge that the Malawi govern ments should maintain and, if they haven’t already, implement programs that support low-income households, such as transfer payments, which have been shown to uplift people out of income poverty in many developing countries